Short Communication Formulation and in vitro Evaluation of a Cosmetic Multiple Emulsion from Olive Oil: Short Communication: Multiple Emulsion from Olive Oil - Akhtar, Naveed; Ahmed, Mahmood; Akram, Marina; Mumtaz, Ahmad Mahmood (Biological Sciences - PJSIR, 2008)
Stability of multiple emulsion prepared using olive oil was evaluated at different storage temperatures. The formulation remained stable at lower temperatures for 28 days without any phase separation. Significant changes in the pH were observed in the formulation, kept at 8 °C from the 5th day onwards, in the electrical conductivity at 40 °C from 14th day onwards and in the globule size, at 40 °C and 40° C + 75% RH condition from 24 h onwards.